KAPABILITAS KEWIRAUSAHAAN DAN PROFITABILITAS: PERAN MODERASI FLEKSIBILITAS STRATEGI - Maria Pampa Kumalaningrum (Fakultas Bisnis UKDW, 2012)
This study to examine the interactive effect between strategic flexibility and entrepreneurial capability on profitability. Entrepreneurial capability refers to a firm’s strategic orientation, which consists of decision-making styles, methods, and practices that can be described as aggressive, innovation, proactive, risk taking, or autonomy seeking. Data was analyzed using moderated regression analysis. The result showed that entrepreneurial capability and strategic flexibility interact to influence firm performance in such way that strategic flexibility enhances the positive relationship between entrepreneurial capability and profitability. Theoretical and managerial implications of the findings are also discussed.Keywords: entrepreneurial capability, flexibility strategic, and profitability